NLRP3 inflammasome-mediated disruption of mitochondrial homeostasis in alveolar macrophages contributes to ozone-induced acute lung inflammatory injury - Miao Xinyi; Li Xinling; Ma Pengwei; Li Mengyuan; Jiang Yuting; Wang Pengpeng; Zhou Xiaolei; Wang Ling; Shang Pingping; Zhang Qiao; Feng Feifei (Acta Biochimica et Biophysica Sinica)
Ozone (O3), a prevalent atmospheric pollutant, can induce lung injury. However, the molecular mechanisms of O3-induced acute lung inflammatory injury remain unclear. In this study, we investigate the abnormal changes in and molecular mechanism of mitochondrial homeostasis in alveolar macrophages (AMs) in O3-induced acute lung inflammatory injury mice. Mitochondria and mitochondrial reactive oxygen species (mtROS) are labeled with Mito-Tracker® Deep Red and MitoSOX Red, respectively. Mitochondrial DNA (mtDNA) in AMs from the bronchoalveolar lavage fluid (BALF) is detected via real-time PCR, and the expressions of mitochondrial fusion/fission-related and biogenesis-related proteins in AMs are determined via immunofluorescence staining. Our data show that in O3-induced acute lung inflammatory injury mice, the number of AMs and the protein expression of the NLRP3 inflammasome complex in the lung tissue are increased. In AMs from O3-exposed mice, the number of mitochondria, mtROS, and fission-related protein DRP1 are increased, but the levels of Na+‐K+‐ATPase, fusion-related protein OPA1, biogenesis-related protein NRF1 and mtDNA are significantly decreased. Compared with that in O3-exposed WT mice, lung inflammation is attenuated, especially the indicators of mitochondrial homeostatic imbalance in AMs, which are alleviated in NLRP3‒/‒ and Caspase-1‒/‒ mice after O3 exposure. These findings indicate that the NLRP3 inflammasome-mediated imbalance in mitochondrial homeostasis in AMs contributes to O3-induced acute lung inflammatory injury. This study may provide a new target for the prevention of lung inflammation induced by O3.